2013
DOI: 10.15288/jsad.2013.74.280
|View full text |Cite
|
Sign up to set email alerts
|

Group Influences on Individuals’ Drinking and Other Drug Use at Clubs

Abstract: This article examines effects of the social group on individual alcohol and drug use upon entry and exit from the club. Based on collected biological measurements of alcohol and other drug use, this study explores whether social group indicators (e.g., group characteristics) are predictive of alcohol and other drug use for individual club patrons. Method: A total of 368 social groups, representing 986 individuals (50.7% female), were anonymously surveyed, and biological measures of alcohol and other drug use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 11 publications
2
54
3
Order By: Relevance
“…This provides the opportunity to collect objective measures of substance use at both entry and exit: breath samples (to test for alcohol) and oral fluid samples (to test for drugs). The Pacific Institute for Research and Evaluation (PIRE) has conducted portal survey studies at the border crossing into Tijuana, Mexico (Johnson, 2012;Johnson & Clapp, 2011;Kelley-Baker et al, 2012;Lange et al, 2006aLange et al, , 2006b, and at the entrances to clubs that feature electronic music (e.g., Johnson et al, 2012;Miller et al, 2005Miller et al, , 2009Miller et al, , 2013aVoas et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides the opportunity to collect objective measures of substance use at both entry and exit: breath samples (to test for alcohol) and oral fluid samples (to test for drugs). The Pacific Institute for Research and Evaluation (PIRE) has conducted portal survey studies at the border crossing into Tijuana, Mexico (Johnson, 2012;Johnson & Clapp, 2011;Kelley-Baker et al, 2012;Lange et al, 2006aLange et al, , 2006b, and at the entrances to clubs that feature electronic music (e.g., Johnson et al, 2012;Miller et al, 2005Miller et al, , 2009Miller et al, , 2013aVoas et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment consisted of randomly approaching groups as they approached the club. Detailed recruitment procedures are presented in prior studies Miller et al, 2013a). Respondents provided informed consent to participate in anonymous research before data collection began.…”
Section: Recruitment and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Both portal [4][5][6][7][8][9][10] and intercept [11][12][13][14] studies have obtained fairly high participation rates using random sampling and are able to measure nonresponse bias. The portal approach, however, has limitations, such as restricting samples to patrons of specific venues and usually requiring the licensee's permission for recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…Authors from different countries found that cannabis products abuse leads to the same adverse effects as of other illicit drugs [3][4][5][6]. The regular use of cannabis products is associated with an increase of the incidence in mental disorders for young people [7].…”
Section: Introductionmentioning
confidence: 99%